2021
DOI: 10.1088/1361-6552/abeac6
|View full text |Cite
|
Sign up to set email alerts
|

Shedding synchrotron light on teacher training

Abstract: This paper aims to introduce the initiative Escola Sirius para Professores do Ensino Médio (ESPEM, Sirius School for High School Teachers) hosted by the Centro Nacional de Pesquisa em Energia e Materiais (CNPEM, Brazilian Center for Research in Energy and Materials) and supported by the Sociedade Brasileira de Física (SBF, Brazilian Physical Society). The program covers the principles and applications of synchrotron radiation with expositive lectures, discussions, and visits to the CNPEM facilities. By using s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Iniciando com [16], esses autores mencionam que os docentes do Ensino Médio possuem poucas oportunidades de aprender e de entender as novas ciências e as tecnologias; os currículos dos cursos de licenciatura em física são obsoletos e desconectados da ciência de ponta, inclusive daquela que a universidade brasileira produz. Desse modo, as aulas de física naquele nível não são capazes de acompanhar a evolução das tecnologias, embora os estudantes demonstrem interesse por isso.…”
Section: Título Do Artigo Autor(es) Anounclassified
“…Iniciando com [16], esses autores mencionam que os docentes do Ensino Médio possuem poucas oportunidades de aprender e de entender as novas ciências e as tecnologias; os currículos dos cursos de licenciatura em física são obsoletos e desconectados da ciência de ponta, inclusive daquela que a universidade brasileira produz. Desse modo, as aulas de física naquele nível não são capazes de acompanhar a evolução das tecnologias, embora os estudantes demonstrem interesse por isso.…”
Section: Título Do Artigo Autor(es) Anounclassified
“…ESPEM (Acioly, 2020(Acioly, , 2021(Acioly, , 2022 is an in-service teacher training course to foster partnerships between teachers and universities (in this case, a research center) to enhance the teaching and learning process in the classroom (Villegas-Reimers, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The Sirius School aims to provide high-quality teacher training by promoting interactions between leading Brazilian science researchers working at the Brazilian Center for Research in Energy and Materials (CNPEM) and participating teachers. This approach emphasizes the importance of establishing links between research laboratories and basic education schools (Acioly, 2020(Acioly, , 2021(Acioly, , 2022. However, communication between academic research and teaching practice remains a significant challenge.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that the involvement of teachers and students in activities involving accelerators and synchrotron facilities has a high impact on education (Arce-Larreta et al, 2021;Micklavina, Almqvist, Sörensen, 2014). Motivated by a recent in service teacher training course in SL, (Acioly et al, 2020;Acioly et al, 2021) , held in the new Brazilian SL source, at the National Center for Energy Research and Materials, Campinas , Brazil, this paper presents alternatives for High School teachers to apply in their classes the contents of physics and existing applications in synchrotron light sources. As these contents need to be taught in some way in the school curriculum, this paper aims to present some strategies to adequately address them.…”
Section: Introductionmentioning
confidence: 99%